PORK QUALITY OF BALINESE PIGS COMMERCIAL RATION WITH SUPPLEMENTATION OF A MIXTURE OF AMINO ACIDS AND CHOLINE - G. R, Daniela; Lindawati, S. A.; Sumadi, I K. (Jurnal Peternakan Tropika; Vol 12 No 2 (2024): Vol. 12 No. 2 Tahun 2024; March - April, 2024)
This study aims to determine the pork quality of Balinese pigs commercial rations supplementation of a mixture of amino acids and choline. The design used was a completely randomized design (CRD) consisting of 4 treatments and 3 replications. The treatments tried were P0: commercial rations; P1: commercial ration + 5% supplementation of a mixture of lysine, methionine, tryptophan and choline from their needs; P2: commercial ration + 10% supplementation of a mixture of lysine methionine, tryptophan and choline from their needs and P3: commercial ration + 15% supplementation of a mixture of lysine, methionine, tryptophan and choline from their needs. The variables observed were protein content, fat content, moisture Submitted Date: June 6, 2023 Accepted Date: September 3, 2023 Submitted Date: November 12, 2020 Accepted Date: January 3, 2021 Editor-Reviewer Article: Eny Puspani & A.A. Pt. Putra Wibawa Editor-Reviewer Article : Ni Putu Mariani & Dsk. Pt. Mas Ari Candrawati Daniela, G. R., Peternakan Tropika Vol. 12 No. 2 Th. 2024: 31 – 47 Page 32 content, pH and total bacteria. The results showed that the pH P2 were significantly different (P<0.05) higher by P0 (control). while the pH of treatment P0, P1 and P3 is relatively the same. Protein content, fat content, water content and total bacteria in all treatments showed no significant differences (P>0.05). The conclusion of this study was that commercial rations supplemented with a mixture of amino acids and choline had no effect on protein content, fat content, water content and total bacteria, but had a good effect on the pH of Balinese pork.